DETERMINAN PERILAKU ORANG TUA TERHADAP PENGAWASAN DALAM PENGGUNAAN GADGET PADA ANAK USIA 7 – 12 TAHUN DI RT 02 RW 02 DUSUN WONOSRI BARAT DESA KOTO TINGGI PASIR PENGARAIAN - Syukaisih Syukaisih; Riri Maharani; Al Hidayati; Risa Amalia; Zulmeliza Rasyid (STIKes Al-Insyirah Pekanbaru, 2022)
Gadgets are among mobile phones that are more powerful than computers. Surveys in some countries prove that 98% of parents allow children to use gadgets. Early surveys conducted with 5 parents at rt 02 rw 02 they just knew the negative effects of gadget could have on a child's eye. When asked about other effects, they were unaware of the implications of the other gadgets. The five parents also said that they left their children gadgets for hours on end. The study aims to find out the relationship of knowledge, attitude, perception and parental communication to supervision in gadgets use of 7-year-olds in rt 02 rw 02 village west wonosri koto tinggi pasir pengaraian. The kind of quantitative descriptive research using a sectional cross. Research conducted at rt 02 rw 02 village west wonosri koto tinggi pasir pengaraian. The population and samples in this study are all 63 year-old mothers with children. Studies suggest that there is a link between knowledge, attitude, perception, and communication with the behavior of a parent toward supervision in the use of gadgets in a child. It is hoped that health workers can do a school promotion on the effects of gadgets use on children. And it's expected that the parents will improve control behavior